Penerapan Logoterapi dalam Menangani Perilaku Hedonis - Nurhidayatullah; Erwan; Muhammad Ilham Bakhtiar (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2021)
This study aims to determine 1) The description of hedonic behavior in SMA Kartika Makassar. 2) The factors behind the hedonic behavior in SMA Kartika Makassar. 3) Implementation of the logotherapy technique on the hedonic behavior of students at SMA Kartika Makassar. This study uses a qualitative approach with clinical case study methods. The subject in this study was one student of SMA Kartika Makassar who showed a behavior that tends to be hedonistic. The results showed that (i) the research subjects showed behavior that tended to be hedonic seen from the behavior based on the characteristics of hedonic behavior (ii) The factors that caused the subjects to behave hedonic were wanting to be recognized in their group, wanting to be popular, following trends, and for self-actualization or identity (iii) Efforts to handle problems carried out on the two subjects identified as experiencing hedonic behavior, namely individual counseling services with logotherapy techniques, namely counseling techniques are techniques that can help counselees find meaning in their lives so as to encourage subjects to change and carry out various activities such as work and work activities so that their lives are felt meaningful and valuable